(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Goitre recurrence is a common problem following subtotal thyroid gland resection for multinodular goitre disease. The aim of the present study was to evaluate morbidity rate in relation to the side of initial and redo-surgery for recurrent disease. METHODS: A total of 1699 patients underwent consecutive thyroid gland surgery between 1997 and 2010 at our institution. One hundred and eighteen patients (6.9%) underwent redo-surgery for recurrent disease after subtotal resection. One hundred and nine patients with complete follow-up were included in the present study. RESULTS: Recurrent disease was found in 79 patients (72.5%) in the ipsilateral lobe and in 30 patients (27.5%) in the contralateral lobe. The incidence of permanent recurrent laryngeal nerve palsy was significantly higher in patients undergoing redo-surgery on the ipsilateral lobe compared to patients undergoing initial operation (3.8% vs. 1.1%; p = 0.03), whereas no difference was found in patients with contralateral redo-surgery compared to patients undergoing initial operation (p = 1.0). Independent risk factors for contralateral recurrent disease were age at primary operation <37 years (OR 4.86; 95% CI 1.58–15.01) and time to recurrence <20 years (OR 6.53; 95% CI 2.23–19.01). CONCLUSION: Morbidity rate for recurrent disease after subtotal resection was significantly higher for ipsilateral redo-surgery compared to initial surgery, whereas redo-surgery can be performed safely on the contralateral lobe. Young age at primary operation and short time to recurrence are independent risk factors for contralateral recurrent disease.